A multimodality imaging-compatible insertion robot with a respiratory motion calibration module designed for ablation of liver tumors: a preclinical study. (17th November 2018) - Li, Dongrui; Cheng, Zhigang; Chen, Gang; Liu, Fangyi; Wu, Wenbo; Yu, Jie; Gu, Ying; Liu, Fengyong; Ren, Chao; Liang, Ping
Abstract: Purpose: To test the accuracy and efficacy of the multimodality imaging-compatible insertion robot with a respiratory motion calibration module designed for ablation of liver tumors in phantom and animal models. To evaluate and compare the influences of intervention experience on robot-assisted and ultrasound-controlled ablation procedures. Methods: Accuracy tests on rigid body/phantom model with a respiratory movement simulation device and microwave ablation tests on porcine liver tumor/rabbit liver cancer were performed with the robot we designed or with the traditional ultrasound-guidance by physicians with or without intervention experience. Results: In the accuracy tests performed by the physicians without intervention experience, the insertion accuracy and efficiency of robot-assisted group was higher than those of ultrasound-guided group with statistically significant differences. In the microwave ablation tests performed by the physicians without intervention experience, better complete ablation rate was achieved when applying the robot. In the microwave ablation tests performed by the physicians with intervention experience, there was no statistically significant difference of the insertion number and total ablation time between the robot-assisted group and the ultrasound-controlled group. The evaluation by the NASA-TLX suggested that the robot-assisted insertion and microwave ablation process performed by physicians with or without experience were more comfortable. Conclusion: The multimodality imaging-compatible insertion robot with a respiratory motion calibration module designed for ablation of liver tumors could increase the insertion accuracy and ablation efficacy, and minimize the influence of the physicians' experience. The ablation procedure could be more comfortable with less stress with the application of the robot.